Curcuma phongvui (Zingiberaceae: Zingiberoideae), a new species from southern Vietnam - Pham, Thi Thanh Dat; Bui, van The Vinh; Tran, van Chen; Nguyen, Khang Sinh; Chen, Juan (Phytotaxa, 2026)
Curcuma phongvui (Zingiberaceae) is described and illustrated here as a new species from Tay Ninh Province in southern Vietnam. The new species, belonging to C. subg. Hitcheniopsis, is morphologically close to C. prasina, but differs in its branched, creeping rhizomes, green lamina with deep reddish-purple along the midrib, green fertile bracts with reddish-purple striations and sub-obtuse and slightly reflexed tips, spatulate lateral staminodes, white labellum with violet stripes and white patches in center and two dark violet lines occasionally with yellow patches, pubescent at base, and creamy-white anthers. Information on distribution, ecology, phenology, vernacular names and a preliminary IUCN conservation assessment are also provided.